Physiological comfort and flame retardancy of fabrics with electrostatic self-assembled coatings - New, Jackie (2017)
Simultaneous improvement of flame retardancy and physiological comfort of clothing fabrics has not been studied before. One of the probable reasons for this is the complexity of dynamic processes involved. This work is a preliminary effort to understand various parameters involved in combining these two facets of fabrics. For this purpose, polyester fabrics are coated with branched polyethylenimine (BPEI) and sodium montmorillonite (smectite clay) via electrostatic self-assembly approach. The effect of their concurrent presence in different concentrations (variation of number of bilayers) on thermo-oxidative properties and flame retardancy behavior as well as physiological comfort (in terms of wicking, moisture management, and air permeability) of polyester has been assessed. The obtained results have shown the efficiency of the electrostatic self-assembly process in improving both facets. This work provides the foundation and knowledge for further development of effective coating systems with a multi-functional approach in the textile industry.